Case studies and theory development in the social sciences - George, Alexander L.; Bennett, Andrew (b)
"The use of case studies to build and test theories in political science and the other social sciences has increased in recent years. Many scholars have argued that the social sciences rely too heavily on quantitative research and formal models and thus have attempted to develop and refine rigorous methods for using case studies. This text presents a comprehensive analysis of research methods using case studies and examines the place of case studies in social science methodology. It argues that case studies, statistical methods, and formal models are complementary rather than competitive."
Includes bibliographical references and index.
Keywords: Social sciences -- Methodology; Social sciences -- Case studies